Still not reconciled yet! : reparation indigenism and the attempt to settle the historical debt with the Marãiwatsédé Xavante in Brazil and the Anishinaabeg of lac seul in Canada - Machado, Clarisse Drummond Martins (2021)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciências Sociais, Centro de Pesquisa e Pós-Graduação sobre as Américas, Programa de Pós-Graduação em Estudos Comparados sobre as Américas, 2021.